Sialorrhea in children with cerebral palsy, - Bruno Leonardo Scofano Dias; Alexandre Ribeiro Fernandes; Heber de Souza Maia Filho
Abstract Objective: To review the literature on sialorrhea in children with cerebral palsy. Source of data: Non-systematic review using the keywords "sialorrhea" and "child" carried out in the PubMed®, LILACS®, and SciELO® databases during July 2015. A total of 458 articles were obtained, of which 158 were analyzed as they were associated with sialorrhea in children; 70 had content related to sialorrhea in cerebral palsy or the assessment and treatment of sialorrhea in other neurological disorders, which were also assessed. Data synthesis: The prevalence of sialorrhea is between 10% and 58% in cerebral palsy and has clinical and social consequences. It is caused by oral motor dysfunction, dysphagia, and intraoral sensitivity disorder. The severity and impact of sialorrhea are assessed through objective or subjective methods. Several types of therapeutic management are described: training of sensory awareness and oral motor skills, drug therapy, botulinum toxin injection, and surgical treatment. Conclusions: The most effective treatment that addresses the cause of sialorrhea in children with cerebral palsy is training of sensory awareness and oral motor skills, performed by a speech therapist. Botulinum toxin injection and the use of anticholinergics have a transient effect and are adjuvant to speech therapy; they should be considered in cases of moderate to severe sialorrhea or respiratory complications. Atropine sulfate is inexpensive and appears to have good clinical response combined with good safety profile. The use of trihexyphenidyl for the treatment of sialorrhea can be considered in dyskinetic forms of cerebral palsy or in selected cases.